Trial of a Family Resilience Instrument with the Rasch Model for Families in the Special Region of Yogyakarta - Ani, Ani; Dwiningrum, Siti Irene Astuti; Astuti, Budi (Bulletin of Counseling and Psychotherapy, 2024)
This study aims to develop an instrument/scale to measure family resilience. A sample of 265 families in the Special Region of Yogyakarta was established using the random sampling technique, with the criteria of families in the Yogyakarta area served by the Office of Religious Affair (KUA), and those who have the Pusaka Sakinah program (Sakinah Family Service Center). The data analysis used Aiken's V content validity coefficient and construct validity used Rasch model analysis. The results of Aiken's V coefficients by three experts show a value range of 0.802. This means that the items in the instrument have a high coefficient for measuring family resilience. In addition, the results of the Rasch model analysis show that the item person has a reliability of 0.97 and the item separation has a reliability of 6.03, which means that the measuring instrument has a good function because it has a range of varying degrees of difficulty. Meanwhile, the subject has a reliability of 0.91 and a person separation has a reliability of 3.17. This shows that the character of the subject varies according to the profile of the respondents who come from various educational backgrounds. All items are valid and reliable for measuring the right construct.